2022
DOI: 10.1155/2022/9382154
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic and Ecological Interaction of Leishmaniasis Vectors (Diptera: Psychodidae) in Sefrou Province (Middle Atlas Morocco)

Abstract: An entomological survey was carried out in the locality of Aichoune to conduct a study on sand flies, species composition, and monthly relative abundance. This study is essential for the implementation of integrated vector management control. Insects collection was carried out twice a month from January 2013 to December 2014 by means of adhesive and CDC-type light traps. A total of 5441 sand flies were collected with the predominance of males (a sex ratio = 1.89). The sampled specimens consist of seven species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The results agree with those obtained in the same region of Fez Meknes, 24,31, especially in the Province of Sefrou. 23,29,30 It was confirmed that the temperature parameter is strongly correlated with the distribution of the seven species of sand flies captured in the Aichoun locality. On the other hand, relative humidity and precipitation do not have a positive effect on the existence and abundance of these species; rather, the correlation is strongly negative.…”
Section: Effect Of Climatic Factors On the Sand Fly Distributionmentioning
confidence: 67%
See 2 more Smart Citations
“…The results agree with those obtained in the same region of Fez Meknes, 24,31, especially in the Province of Sefrou. 23,29,30 It was confirmed that the temperature parameter is strongly correlated with the distribution of the seven species of sand flies captured in the Aichoun locality. On the other hand, relative humidity and precipitation do not have a positive effect on the existence and abundance of these species; rather, the correlation is strongly negative.…”
Section: Effect Of Climatic Factors On the Sand Fly Distributionmentioning
confidence: 67%
“…On the other hand, relative humidity and precipitation do not have a positive effect on the existence and abundance of these species; rather, the correlation is strongly negative. 23,29,30 The impact of climatic factors on the abundance of this fauna was researched on another biotope in Meknes prefecture, revealing a strong positive correlation between temperature and the different species of phlebotomine, and a negative correlation between humidity and phlebotomine activity was also confirmed. 24 Correlations between the studied parameters According to Table 3, the majority of correlation coefficients are positive, indicating a direct and significant relationship between the above variables in the study area.…”
Section: Effect Of Climatic Factors On the Sand Fly Distributionmentioning
confidence: 89%
See 1 more Smart Citation
“…In Morocco, Ph. sergenti is known as a widespread species throughout the country and predominant in the arid and Saharan areas [45][46][47]. Te vector is abundant in rural areas as well as in the habitats of the urban population [48].…”
Section: Discussionmentioning
confidence: 99%
“…In the same region of Fez Meknes (ex. Fez-Boulmane), particularly in Moulay Yakoub province, 31, and Sefrou Province, 32,33 temperature and humidity are the main parameters of the biological evolution of the disease. The phlebotomine density in Ouled Aid reaches its maximum when the temperature is between 30 and 35°C.…”
Section: Seasonal Fluctuations Of Sand Flies and The Effect Of Climat...mentioning
confidence: 99%